Streamlined object modeling patterns, rules, and implementation - Nicola, Jill (Prentice Hall PTR, 2002)
CD-ROM contains: Book's source code (in both Java and Squeak) -- Virtual machine installers for Java Software Development Kit 1.3.1 and Squeak 3.0 -- Links to Web sites, mailing lists, and newsgroups for Java and Squeak developers.
Includes bibliographical references (pages 343-344) and index. - Print version record
Keywords: Object-oriented methods (Computer science); Conception orientée objet (Informatique)